Child neglect, psychological abuse and smartphone addiction among Chinese adolescents: The roles of emotional intelligence and coping style. (January 2019) - Sun, Jianing; Liu, Qinxue; Yu, Si
Abstract: The present study examined the mediation effects of emotional intelligence and coping style between child neglect and psychological abuse and smartphone addiction. A sample of 1041 Chinese adolescents from 11 to 15 years of age (mean age = 12.41 years, SD = 0.65) responded to anonymous questionnaires regarding child neglect and psychological abuse, emotional intelligence, coping style and smartphone addiction. The findings revealed that both emotional intelligence and coping style mediated the link between child neglect and psychological abuse and smartphone addition in a parallel fashion. In addition, emotional intelligence and coping style also sequentially mediated the link between child neglect and psychological abuse and smartphone addiction. The present study can contribute to a better understanding of how child abuse and neglect increased the risk of smartphone addiction. It suggests that tailored approaches are necessary for adolescents who are addicted to smartphones. Highlights: Child neglect and psychological abuse were significant predictors of smartphone addiction. Emotional intelligence mediated the associations between child neglect and psychological abuse and smartphone addiction. Coping style mediated the associations between child neglect and psychological abuse and smartphone addiction. Emotional intelligence and coping style not only parallelly but also sequentially mediated the above associations.